Dendritic cell-targeted theranostic nanomedicine: Advanced cancer nanotechnology for diagnosis and therapy - Mehata, A.K.; Viswanadh, M.K.; Priya, V.; Vikas, V.; Muthu, M.S. (Future Medicine Ltd., 2020)
No abstract available
Keywords: dendritic cells; drug targeting; safety; theranostics; upconversion nanoparticles